INTUITIONISTIC FUZZY... ... - SARAVANAKUMAR, G.; TAMILSELVAN, S.; VADIVEL, A. (International Journal of Mathematical Archive, 2018)
This paper is devoted to the study of new class of sets called an intuitionistic fuzzy -locally closed sets, intuitionistic fuzzy -sets, intuitionistic fuzzy -locally closed sets and intuitionistic fuzzy - -locally closed sets are introduced and studied. Also the concepts of an intuitionistic fuzzy - -locally closed set intuitionistic fuzzy subspace, intuitonistic fuzzy - -local- -semi (resp., -pre and ) spaces are introduced and interesting properties are established. In this connection, interrelations are discussed. Examples are provided where necessary.